Unravelling adolescent girls' aspirations in Nepal: Status and associations with individual-, household-, and community-level characteristics. - Dónya S Madjdian (Public Library of Science (PLoS), 2021)
Background Adolescents' aspirations have potential to influence their present and future well-being. Limited knowledge exists on adolescent girls' aspirations and their determinants, particularly in low-income contexts. Methods and findings Using cross-sectional data, collected in 2018 in Nepal, within the Suaahara II Adolescent Panel Survey, (n = 840), adolescent girls' aspirations in several domains-education, occupation, marriage, fertility, health, and nutrition-were described. Regression models were estimated to explore associations between individual, household and community characteristics and these aspirations for all adolescents and separately for younger (10-14 years) and older (15-19 years) girls. Age, school attendance, and self-efficacy, as well as household wealth, caste/ethnicity, size, and agro-ecological zone of residence were significantly associated with aspirations, although effect sizes and significance varied by aspiration domain and age group. Conclusions Findings underscore the curtailing effect of poverty on aspirations and the dynamic nature of aspirations. Initiatives to foster girls' aspirations must address both individual and contextual factors.